INTEGRATION OF VIDEO COMMUNICATION AND AUGMENTED REALITY PLATFORMS INTO THE MODEL OF BLENDED AND DISTANCE LEARNING LESSONS IN GENERAL SECONDARY EDUCATION INSTITUTIONS - Sukhikh, Alisa (Physical and Mathematical Education, 2025)
Formulation of the problem. The current transformation of the educational process has highlighted the need to find effective solutions for organizing blended and distance learning in secondary schools. Despite the widespread use of video conferencing platforms (such as Zoom, Meet, Teams), the educational process in digital format is often accompanied by a decrease in student engagement, monotony in the presentation of material, information overload, and a lack of flexible didactic solutions capable of taking into account the age, cognitive, and motivational characteristics of modern generations of students. In this context, immersive technologies, especially augmented reality, have significant potential for building a visually rich, interactive, and emotionally engaging educational environment. At the same time, within the framework of general secondary education in Ukraine, the possibilities of integrating AR content with synchronous interaction platforms into the structure of school lessons have not been sufficiently researched and methodologically standardized. This creates a demand for the development of models that would ensure the pedagogical integrity of such a combination and contribute to the more effective use of EdTech in the learning process. Materials and methods. The study uses theoretical methods, including analysis of scientific, methodological, psychological, and pedagogical literature on blended and distance learning, digital pedagogy, and pedagogical design, taking into account the age characteristics of different generations. Results. The main problems of distance and blended learning in secondary schools have been identified, in particular, reduced attention, limited visualization, and content overload. Based on an analysis of the age characteristics of the Zumer and Alpha generations, the feasibility of integrating AR content in combination with video communication platforms has been substantiated. A typical selection of lesson models with immersive elements has been developed, adapted to the subject area, age of students, and learning format. Conclusions. The integration of video communication platforms with AR content helps to increase the effectiveness of short-distance and blended lessons, engages students, and supports their cognitive needs. The proposed models and the catalog of immersive services can be used by teachers as a tool for updating lessons. Full implementation requires digital training for teachers and institutional support for immersive approaches in schools.